Perceptions of hiv- positive women towards sexual experiences - Maria Wanderleya de Lavor Coriolano; Emery Ciana Figueiredo Vidal; Eglídia Carla Figueiredo Vidal (Rev Rene)
AIDS, as complex subject, mobilizes for the public sphere, parameters relegated to the private sphere. It also unveils privatecourt questions, which are particular of the sexual area. Our objective with this study was to understand the implications of the positive serology for HIV in the sexuality of women who live with the disease. It's a qualitative and descriptive study, carried out from May to June 2006 using semi-structured interview with 12 users from the Clinic of Infectlogy in Juazeiro do Norte-CE. By the technique of content analysis four categories had been established: 1. Sexual sphere: changes in the sexual practices; 2. types of experienced sexual practices; 3. Meaning of the condom; 4. the sexual desire. Gender roles are decisive for their practices, sensations of pleasure and use of the condom, in which gender inequality are shown as a massive component, calling attention to the feminine fragility front to the exercise of its sexuality and the process of being and feeling of the individual.